Identification of Acidic Triterpenoid Saponins from Silene vulgaris Using a Methylation-Based Isolation and LC-MS Analysis Strategy - Kikuchi, Takashi; Liu, Danyang; Otsuki, Kouharu; Koike, Kazuo; Li, Wei (Chemical & pharmaceutical bulletin, 2025)
The Silene genus plants in the Caryophyllaceae family are a large genus with over 850 species. It has been known that Silene genus plants contain triterpenoid saponins. These saponins have glucuronic acid in the sugar chain and are difficult to separate in chromatography. In this study, a strategy was developed to clarify the distribution of triterpenoid saponins in whole plants of Silene vulgaris by isolation of neutralized saponins using methylation reactions, which were used as standard substances for LC-MS analysis, and elucidating their characteristic MS and MS/MS fragment patterns. The n-butanol fraction of the methanol extract from the whole plant of S. vulgaris was separated to obtain fractions including saponins by octadecyl silica column chromatography. Then, each fraction was treated with trimethylsilyl diazomethane for methylation of the carboxyl groups of glucuronic acid in the molecules, and five triterpenoid methylated saponins (7a, 13a, 14a, 16a, and 17a) were isolated using HPLC. The chemical structures of the isolated compounds were determined by spectroscopic analyses including NMR and MS, and their characteristic fragmentations were also clarified in LC-MS and MS/MS. It was performed on the n-butanol fraction from the whole plant of S. vulgaris, and the chemical structures of 22 triterpenoid saponins were estimated based on the MS and MS/MS fragmentation patterns of the isolated triterpenoid saponins.